Prophage Induction in Escherichia coli (Lambda) by N-Nitrosamines - Thomson, Jennifer A. (1975)
Carcinogenic N-nitrosamines were tested for their ability to induce λ in a lysogenic strain of Escherichia coli K-12 (58-161 F(+)). Dimethylnitrosamine, di-n-propylnitrosamine, methyl-n-propylnitrosamine, and N-nitrosopiperidine were shown to be inducers of prophage.